theorem ntheqd (_G: wff) (_n1 _n2 _l1 _l2: nat): $ _G -> _n1 = _n2 $ > $ _G -> _l1 = _l2 $ > $ _G -> nth _n1 _l1 = nth _n2 _l2 $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
hyp _nh |
_G -> _n1 = _n2 |
|
2 |
hyp _lh |
_G -> _l1 = _l2 |
|
3 |
_G -> len _l1 = len _l2 |
||
4 |
_G -> (_n1 < len _l1 <-> _n2 < len _l2) |
||
5 |
_G -> listfn _l1 = listfn _l2 |
||
6 |
_G -> listfn _l1 == listfn _l2 |
||
7 |
_G -> listfn _l1 @ _n1 = listfn _l2 @ _n2 |
||
8 |
_G -> suc (listfn _l1 @ _n1) = suc (listfn _l2 @ _n2) |
||
9 |
_G -> 0 = 0 |
||
10 |
_G -> if (_n1 < len _l1) (suc (listfn _l1 @ _n1)) 0 = if (_n2 < len _l2) (suc (listfn _l2 @ _n2)) 0 |
||
11 |
conv nth |
_G -> nth _n1 _l1 = nth _n2 _l2 |